KING ALFRED THE GREAT, HIS HAGIOGRAPHERS AND HIS CULT - Kalmar, Toma??s Mario, 1942- Link ([S.l.])
1 online resource
Keywords: This book situates Alfred the Great in his hagiographic context. For 150 years, the fables told in the ninth century about Alfred's childhood have posed interlocking disciplinary challenges to historians committed to evicting romance from history. Blending current Hagiography Studies with historical, literary, and biblical hermeneutics can help us forgo the anti-hagiographic commitments which motivated the scholars who purified the Victorian cult of Alfred by expunging his legends and salvaging his historicity. The book focusses on the typological functions of three Alfredian fables from the Old English Chronicle, the Old English Boethius, and Asser's Vita lfredi, analyses the plot common to all three, critiques the psychological conjecture that Alfred's childhood memory was their common source, and shows that synoptically they can help us see how Alfred shaped the curve of his own life's destiny and how he engaged in the formation of his own cult to last a thousand years.